Neurotherapy of Yi-Gan-San, a Traditional Herbal Medicine, in an Alzheimer’s Disease Model of Drosophila melanogaster by Alleviating Aβ42 Expression - Ming-Tsan Su; Yong-Sin Jheng; Chen-Wen Lu; Wen-Jhen Wu; Shieh-Yueh Yang; Wu-Chang Chuang; Ming-Chung Lee; Chung-Hsin Wu (Plants, 2022)
Alzheimer’s disease (AD), a main cause of dementia, is the most common neurodegenerative disease that is related to the abnormal accumulation of amyloid β (Aβ) proteins. Yi-Gan-San (YGS), a traditional herbal medicine, has been used for the management of neurodegenerative disorders and for the treatment of neurosis, insomnia and dementia. The aim of this study was to examine antioxidant capacity and cytotoxicity of YGS treatment by using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays in vitro. We explored neuroprotective effects of YGS treatment in alleviating Aβ neurotoxicity of Drosophila melanogaster in vivo by comparing survival rate, climbing index, and Aβ expressions through retinal green fluorescent protein (GFP) expression, highly sensitive immunomagnetic reduction (IMR) and Western blotting assays. In the in vitro study, our results showed that scavenging activities of free radical and SH-SY5Y nerve cell viability were increased significantly (p < 0.01–0.05). In the in vivo study, Aβ42-expressing flies (Aβ42-GFP flies) and their WT flies (mCD8-GFP flies) were used as an animal model to examine the neurotherapeutic effects of YGS treatment. Our results showed that, in comparison with those Aβ42 flies under sham treatments, Aβ42 flies under YGS treatments showed a greater survival rate, better climbing speed, and lower Aβ42 aggregation in Drosophila brain tissue (p < 0.01). Our findings suggest that YGS should have a beneficial alternative therapy for AD and dementia via alleviating Aβ neurotoxicity in the brain tissue.